Hand washing agents and surface disinfectants in times of Coronavirus (COVID-19) outbreak - Kapoor, Abhilasha; Saha, Rumpa (Indian Journal of Community Health, 2020)
Coronavirus pandemic has led to thousands of cases and hundreds of deaths worldwide. India, too, is on the verge of this health risk at the national scale. The only measures to prevent this pandemic from spreading are physical distancing, hand hygiene, and surface disinfection, and wearing of appropriate masks. Many hand sanitizers and surface cleaning agents are being made available which are being claimed to be virucidal and to be effective against coronavirus. Here, we present a review of the hand washing agents and surface disinfectants which have virudical properties and are effective against coronaviruses. This review will help dispel misconceptions about various hand washing agents and surface disinfectants and also help to make informed decisions regarding these items.